The Effect of Spatial Dependence and Population Density on the Economic Development in Banten Region Before and During the Covid-19 Pandemic - Dewiana Novitasari; Shofwatun Hasna; Tias Pramono; Sukriyah Sukriyah; Albertus Maria Setyastanto (Universitas Muhammadiyah Enrekang, 2022)
This study aims to analyze the effect of spatial linkages and population density on economic development in Banten Province in 2016-2021. The data used is panel data with a spatial econometric approach. The selected model is a spatial panel model with fixed effects. This study builds two models, namely, the first model does not include the pandemic period and the second model includes the pandemic period. The results of the analysis of the first model show that before the COVID-19 pandemic occurred, spatial linkages and population density were proven to have a significant positive effect on Banten's per capita income. Population density is the main factor that strongly influences the per capita income of the Banten region. Meanwhile, in the second regression model, spatial correlation is proven to have a significant positive effect on Banten's per capita income, but population density has a negative effect. High population density actually lowers GDP per capita, because there is a lot of unemployment during the pandemic.